Medieval statecraft and the perspectives of history : essays by Joseph Strayer - Strayer, Joseph R. (Joseph Reese), 1904-1987 (Princeton legacy library., 2015)
This collection of essays by the eminent historian Joseph Strayer makes available in one volume his important shorter studies on the central theme of the political, constitutional, and institutional history of France and England in the twelfth and thirteenth centuries. Originally published in 1971.